Cortesía lingüística en el aprendizaje/enseñanza del italiano L2 - Guil, Pura (Cuadernos de Filología Italiana, 2007)
With the aim of sensitizing Italian L2 learners with regards to the problems concerning linguistic politeness, this paper offers an ordered index of possible linguistic mecanisms linked to politeness strategies.